Transformacja sił zbrojnych Federacji Rosyjskiej w latach 1992-2022. Od demobilizacji do konfrontacji - Kajetanowicz, Jerzy (Przegląd Wschodnioeuropejski, 2026)
Russia’s armed forces play an important role in ensuring the country’s security and international position. Their initial composition significantly burdened the budget of stagnant Russia, which was unable to maintain such a large army. The process of transformation of the Russian army began immediately after its formation. In the 1990s, the introduced changes boiled down to reducing the number of soldiers and disbanding poorly trained military units. It was only in the first decade of the 21st century that the search for optimal organizational solutions began to be sought, allowing for the maintenance of a small, but well-trained and ready to defend the country army. However, the scope of these reforms did not meet the expectations of the state authorities, which, in the face of the growing competition between the great powers, decided that only a sufficiently large armed force would guarantee Russia’s effective actions on the international arena. Hence, the second and the beginning of the third decade of the 21st century was a period of intensive reorganization of the Russian army, combined with the modernization of the armament and increasing combat readiness. As a result of these actions, the Russian armed forces were ready to take confrontational actions, which was reflected in the aggression against Ukraine in February 2022.